Pediatric dog bite injuries in the USA: a systematic review. Issue 2 (7th February 2022) - Patterson, Kelli Nicole; Horvath, Kyle Z; Minneci, Peter C; Thakkar, Rajan; Wurster, LeeAnn; Noffsinger, Dana L; Bourgeois, Tran; Deans, Katherine J
Abstract : Introduction: Dog bites are one of the leading causes of non-fatal emergency room visits in children. These injuries not only cause physical harm but can lead to long-term psychological stress. This study evaluated the current literature related to pediatric dog bite injuries to identify research gaps which should be prioritized to improve a major public health concern. Methods: We performed a keyword search of PubMed, Scopus, and OVID Medline databases (January 1980– March 2020) for all published studies focused on dog bite injuries in the pediatric population (≤18 years of age) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results: Out of 1859 abstracts screened, 43 studies involving 86 880 patients were included. Twenty-nine studies were retrospective chart reviews characterizing the epidemiology of dog bites and their associated treatment outcomes; six were prospective cohort studies; two were cross-sectional studies; and six were experimental studies. Synthesized results demonstrate that children <9 years of age suffer the greatest burden of injuries, with children <6 years of age at higher risk of more severe injuries involving the head, neck, and face. Conclusion: Studies analyzing the prevention or psychosocial consequences of dog bites injuries are needed.